2002
DOI: 10.1128/jvi.76.19.10015-10019.2002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Zidovudine- or Lamivudine-Resistant Human Immunodeficiency Virus Type 1 Reverse Transcriptases Containing Mutations at Codons 41, 184, and 215

Abstract: Six structures of human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) containing combinations of resistance mutations for zidovudine (AZT) (M41L and T215Y) or lamivudine (M184V) have been determined as inhibitor complexes. Minimal conformational changes in the polymerase or nonnucleoside RT inhibitor sites compared to the mutant RTMC (D67N, K70R, T215F, and K219N) are observed, indicating that such changes may occur only with certain combinations of mutations. Model building M41L and T215Y i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 25 publications
4
38
0
Order By: Relevance
“…This hypothesis is challenged by kinetic data as well as by mutagenesis studies that fail to show an effect of 215Y on RT affinity for ATP and suggest instead that this mutation optimizes the orientation of ATP for the primer excision reaction (29,35). Our finding of higher rates of primer unblocking in the 67N/70R/219Q enzyme compared to the 41L/210W/215Y enzyme is consistent with the latter model that shows that the 67N/70R/219Q cluster in the absence of changes at the 215 position is also well positioned to make direct contact with ATP which facilitates a catalytically efficient alignment with the primer terminus (8).…”
Section: Discussionsupporting
confidence: 80%
“…This hypothesis is challenged by kinetic data as well as by mutagenesis studies that fail to show an effect of 215Y on RT affinity for ATP and suggest instead that this mutation optimizes the orientation of ATP for the primer excision reaction (29,35). Our finding of higher rates of primer unblocking in the 67N/70R/219Q enzyme compared to the 41L/210W/215Y enzyme is consistent with the latter model that shows that the 67N/70R/219Q cluster in the absence of changes at the 215 position is also well positioned to make direct contact with ATP which facilitates a catalytically efficient alignment with the primer terminus (8).…”
Section: Discussionsupporting
confidence: 80%
“…So far, no crystal structure has been reported for RT that contains bound PP i , ATP, or foscarnet; however, since PP i is derived from the ␤ and ␥ phosphates of the incoming dNTP, it is possible to infer which residues are likely to interact with PP i from the crystal structure of the RT-dTTP-primer-template complex (3,6,16,32,46). If this inference is correct, then RT must adopt a closed configuration to allow residue 65 to interact with PP i and, by extension, with ATP or foscarnet (compare Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using a large sample size (66,224 genotypes), we found that K65R shows a strong negative association with specific TAMs, including M41L, D67N, L210W, T215F/Y, and K219Q/E. TAMs facilitate the excision reaction by increasing binding of ATP through substitutions at 210 and 215 (6,48). M41L and D67N may enhance the effect of T215F/Y by altering the interaction of the 3Ј-azido group of AZT with the dNTP binding pocket, favoring excision (33).…”
Section: Discussionmentioning
confidence: 99%